From liberal to conservative: shifting cultural policy regimes in post-Soviet Russia. Issue 3 (4th May 2018) - Jakobson, Lev I.; Rudnik, Boris; Toepler, Stefan
Abstract : In this paper, we analyze the evolution of Russian cultural policy from the end of the Soviet era through the current against the framework of welfare state regimes. The end of the Soviet Union 25 years ago ushered in a decade of liberalization marked by a withdrawal of the state from cultural responsibility and hopes that market demand and private support would emerge to fill in the void. With the latter hampered by the economic hardships of the transition and the loss of philanthropic traditions after more than 70 years of communism, a liberal policy regime did not take firmly hold and has gradually been replaced by a new cultural policy consensus more akin to a conservative welfare regime, marked by a return of the state to a more dominant role with the support of core cultural policy constituencies.